Interferon-inducible lncRNA IRF1-AS represses esophageal squamous cell carcinoma by promoting interferon response. (10th September 2019) - Huang, Jianbing; Li, Jiagen; Li, Yuan; Lu, Zhiliang; Che, Yun; Mao, Shuangshuang; Lei, Yuanyuan; Zang, Ruochuan; Zheng, Sufei; Liu, Chengming; Wang, Xinfeng; Li, Ning; et al.
Abstract: Interferons (IFNs) play crucial roles in the development and treatment of cancer. Long non-coding RNAs (lncRNAs) are emerging molecules involved in cancer progression. Here, we identified and characterized an IFN-inducible nuclear lncRNA IRF1-AS (Interferon Regulatory Factor 1 Antisense RNA) which was positively correlated with IRF1 expression. IFNs upregulate IRF1-AS via the JAK-STAT pathway. Knockdown and overexpression of IRF1-AS revealed that IRF1-AS inhibits oesophageal squamous cell carcinoma (ESCC) proliferation and promotes apoptosis in vitro and in vivo. Mechanistically, IRF1-AS activates IRF1 (Interferon Regulatory Factor 1) transcription through interacting with ILF3 (Interleukin Enhancer Binding Factor 3) and DHX9 (DExH-Box Helicase 9). In turn, IRF1 binds to the IRF1-AS promoter directly and activates IRF1-AS transcription. Global analysis of IRF1-AS–regulated genes indicated that IRF1-AS activates the IFN response in vitro and in vivo. IRF1 knockdown in IRF1-AS–overexpressing cells abolished the antiproliferative effect and activation of the IFN response. Furthermore, IRF1-AS was downregulated in ESCC tissues, and low expression correlated with poor prognosis. In conclusion, the interferon-inducible lncRNA IRF1-AS represses esophageal squamous cell carcinoma progression by promoting interferon response through a positive regulatory loop with IRF1. Highlights: IRF1-AS is a downregulated tumor suppressive lncRNA in ESCC whose low expression predicts poor prognosis. IRF1-AS is induced by IFNs through JAK-STAT pathway which in turn activates IFN response. IRF1-AS and IRF1 form a positive regulatory loop through mutual transcriptional activation.